EFEKTIVITAS PERATURAN DAERAH KOTA PAYAKUMBUH NOMOR 5 TAHUN 2007 DALAM PENERTIBAN ANAK PUNK - Bayu Krisna Ardiansyah; Faisal Hidayat Ardiansyah (Fakultas Hukum Tata Pemerintahan, 2020)
The entry of one of the foreign cultures caused by the development of the globalization era in the world, namely in the youth community in Indonesia, this culture has led to several changes in the social community of this new teenager which is called the Punk Child. This study aims to determine how the effectiveness of Payakumbuh City Regulation Number 5 of 2007 in Control of Punk Children in Payakumbuh City, West Sumatra. Researchers use research methods with qualitative methods with an inductive approach. Through analysis in a different perspective from previous research, namely, several determinants in public policy as determinants of public policy outcomes. The results of this study are the Child Punk Control has not been effective well because the main goal has not been achieved, the imposition of sanctions that are still not firm and the resources involved are lacking, expertise and skills are still lacking due to members of the Payakumbuh Municipal Civil Service Police Unit. As well as the lack of facilities and facilities from the Civil Service Police Unit in terms of mobility of members and it needs special attention from the government for budgeting. The conclusion of this study shows that the local regulations have not been effective in overcoming the control of punk children in Payakumbuh City. Researchers suggest that the government and police conduct special coaching for job training programs so that punk children are able to live a good life.